Integrasi Pembayaran Pamsimas Desa Dermaji dengan PPOB Menggunakan Web Service - Trias Bratakusuma; Edi Kuswanto (Politeknik Negeri Cilacap, 2019)
The purpose of this research is to design and build an application with the benefit of technology to produce a smart app in form of pamsimas payment with PPOB web service for dermaji village that still uses conventional method till this day. This pamsimas payment app was hoped to help the pamsimas payment process to dermaji villagers so that it'll be easier for them to do the payment. The app was designed in a way that it's as responsive as possible with the Hypertext preprocessor (PHP) and framework CodeIgniter to help the user to use and access this web service